Contributions to the Bryological Knowledge of Aspa 125 Fildes Peninsula, King George Island - Zuniga-Navarro, G (BioMed Central Ltd., 2018)
Background: With 29 Km 2 , the Fildes Peninsula is the largest ice free area in King George Island and probably in Antarctica. The region is house of six permanent bases including the only airport in the South Shetlands, which led to impacts on its original landscape and vegetation. In recognition for the need to protect natural values, an Antarctic Specially Protected Area (ASPA 125) was established in the region. Focused mostly on protecting the fossils, the ASPA also plays a role in protecting the vegetation but so far, the management plan for the area does not contain a list of moss species present there. Results: We provided an updated study and checklist of mosses present in ASPA 125. A key to species identification and photographs of main morphological features are also available in this paper. Also, six new occurrences are reported for Fildes Peninsula. Conclusion: Considering the scarce knowledge about specific local floras in Antarctica associated with highly impacted area, of which only a fraction is protected, it is suggested the necessity to invest in detailed sampling studies, as well as in a better understanding of the local floras interactions in Antarctica. © The Author(s) 2017.